Comparative Effectiveness and Safety of Dabigatran and Rivaroxaban in Atrial Fibrillation Patients - Chao‐Lun Lai; Ho‐Min Chen; Min‐Tsun Liao; Ting‐Tse Lin; K. Arnold Chan (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2017)
BackgroundWe aimed to examine the comparative effectiveness and safety between dabigatran and rivaroxaban in atrial fibrillation patients. Methods and ResultsWe conducted a population‐based, retrospective, new‐user cohort study based on the National Health Insurance claims database in Taiwan. Adult atrial fibrillation patients who initiated dabigatran (N=10 625) or rivaroxaban (N=4609) between June 1, 2012 and May 31, 2014 were identified as the overall population. A propensity score was derived using logistic regression to model the probability of receipt of rivaroxaban as a function of potential confounders. Altogether, 4600 dabigatran users were matched with 4600 rivaroxaban users to create a propensity score–matched population. The marginal proportional hazards model was applied among the propensity score–matched population as the primary analysis, and the proportional hazards model with adjustment of the quintiles of the propensity score among the overall population was used as the secondary analysis. Rivaroxaban users had a higher risk of all‐cause death than dabigatran users (hazard ratio 1.44, 95%CI 1.17‐1.78 in the primary analysis and hazard ratio 1.47, 95%CI 1.23‐1.75 in the secondary analysis). Rivaroxaban users also possessed a higher risk of gastrointestinal hemorrhage needing transfusion than dabigatran users in the primary analysis (hazard ratio 1.41, 95%CI 1.02‐1.95), but the difference diminished in the secondary analysis (hazard ratio 1.20, 95%CI 0.92‐1.56). The risks of ischemic stroke, acute myocardial infarction, arterial embolism/thrombosis, and intracranial hemorrhage were similar between the 2 groups. ConclusionsRivaroxaban therapy was associated with a statistically significant increase in all‐cause death compared with dabigatran therapy in atrial fibrillation patients.